RESEARCH OF FORMATION LEVELS INTELLECTUAL SKILLS OF HIGH SCHOOL STUDENTS - Lovyanova, I.V. (Pedagogy of Higher and Secondary Education, 2007)
In article results of an experimental research of levels of formation intellectual skills logically to operate with a teaching material at learning senior classes of secondaiy school are submitted.